Spatial Variability of Climatic Drought in the Benghazi Plain Using the (SPI) and Johnson’s Continentality–Oceanity Index (1981–2024) (Journal of Libya for geographical studies, 2026)
This study aims to analyze climatic drought in the Benghazi Plain over the period 1981–2024 by integrating two climate indices of different natures: the Standardized Precipitation Index (SPI) and Johnson’s continentality–maritime index. The analysis is based on monthly data obtained from the NASA POWER database. Four observation points were selected and distributed from the coastal zone toward inland areas to represent the climatic gradient between maritime and continental influences. The SPI results reveal a clear gradient in drought severity from the northern coastal areas toward the semi-desert southern parts of the plain, while Johnson’s index indicates a steady increase in continentality along the same direction. Statistical analysis of the relationship between the two indices shows a negative correlation, reflecting the interaction between precipitation-related and thermal factors in shaping drought conditions. Furthermore, spatial analysis using the Kriging interpolation method demonstrates a notable spatial correspondence between increased continentality and higher drought severity in the southern areas, contrasted with relatively moderate conditions along the coast. These findings highlight the importance of integrating precipitation-based and thermal indices with spatial analysis to better interpret the dynamics of climatic drought in the Benghazi Plain.
Keywords: Climatic drought; Standardized Precipitation Index (SPI); Johnson’s continentality–maritime index; spatial analysis; Benghazi Plain